Towards emotional intelligence and quality of work life: Improving the role of work attitude - Achmad Sudiro; Agung Nugroho Adi; Noora Fithriana; Muhammad Fajrul Iskam Fasieh; Mochamad Soelton (Cogent Business & Management, 2023)
This study aims to examine whether the main job attitudes (job satisfaction, job involvement, employee engagement, organizational commitment, and perceived organizational support) mediate the relationship between emotional intelligence and Quality of Work Life (QWL) or not. This study employed a survey design involving employees from various industries at various levels around Indonesia. We distributed 400 questionnaires to the respondents, and the response rate was 81%. Path analysis using SmartPLS 3.0 was used to check the validity and reliability of the questionnaires. Findings. Findings confirmed that employee satisfaction, employee involvement, and perceived organizational support mediated emotional intelligence and quality of work-life. However, employee engagement and organizational commitment did not mediate the relationship between emotional intelligence and the quality of work-life. Limitations. Our study covered a relatively small scope; thus, it is suggested that further studies involve more respondents and regions. Uniqueness. This research explained the mediation effect of major job attitudes based on the Robbins Model, and this was the first time the model was tested in Indonesia.
Keywords: 650; emotional intelligence; employee engagement; employee involvement; employee satisfaction; organizational commitment; ouality of work life (QWL); perceived organizational support (POS)